“For an Autonomy with a General, Socialized Horizon”: An Art Theory of Reform - Feiss, E.C. (The Nordic Journal of Aesthetics, 2025)
Drawing on important incursions of Marxist feminism into art history and theory, this article proposes a more capacious idea of reform as an extension of the historical sites and potential critical ramifications of social reproduction as an art theoretical framework. Social reproduction theory has altered the accepted bifurcation of autonomy and social engagement as two poles of Marxist aesthetics. I offer both a methodological addendum to existing employment of a social reproduction analytic for art, especially as this literature has mainly focused on post-medium practices after the late 1960s. Moreover, I ask what a dialectical concept of reform—as revolutionary and counterrevolutionary simultaneously—does to existing ideations of artistic criticality predicated on autonomy. I endeavor to theorize reform to explain the art of the painter and organizer Betty Blayton in the late 1960s. That Blayton’s art takes the form of color field painting—the idiom of reactionary conservatism in the immediate postwar decades—is unimaginable within most treatments of critical art practice after conceptual art, indeed it is usually the constitutive exclusion. Working through the pertinent literature on social reproduction and artistic autonomy, as well as revisiting canonical texts, I argue that an art theory of reform introduces a distinct form of artistic subjectivity that simultaneously undertakes and references the labor which undergirds art and is its condition of appearance. This artistic labor is distinct from performance or social practice art in its maintenance of the constitutive separation between art and devalorized reform (as reproductive) work. By extension, this split artist subject exceeds—encompasses, if not sidesteps—critique defined by negation. In accepting a relative invisibility stemming from its incomplete negation, such practices risk the slander “reform or reformist.”